2010
DOI: 10.2109/jcersj2.118.903
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the cone crack and fracture mode in ceramics under high-velocity-projectile impact

Abstract: Ceramics will be widely used for enhancing the efficiency of power generating systems, particularly gas turbines. However, ceramics used in these systems suffer damage owing to impact by foreign objects. In this study, various ceramic plates are impacted by a spherical projectile with an impact velocity of 320 m/s. The volume of the cone cracks formed on the plates decreases with an increase in the fracture toughness of the ceramic material. No cone cracks are formed on the zirconia (3Y-TZP) plate because crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In contrast, the crack propagation in ANZ composition was in the intergranular mode. These results coincide with the conclusion of Yamada et al [33] that the volume of the cone is smaller, and more energy was consumed for intergranular-fractured specimens. During the early stages of penetration into a ceramic armour material, both intergranular and transgranular fracture mode are likely to occur, and intergranular cracking is more bene cial in terms of resistance to penetration because the cracks have to follow along more convoluted pathways around the grains, thus increasing the time for fragmentation to occur [11].…”
Section: Cone Formationsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the crack propagation in ANZ composition was in the intergranular mode. These results coincide with the conclusion of Yamada et al [33] that the volume of the cone is smaller, and more energy was consumed for intergranular-fractured specimens. During the early stages of penetration into a ceramic armour material, both intergranular and transgranular fracture mode are likely to occur, and intergranular cracking is more bene cial in terms of resistance to penetration because the cracks have to follow along more convoluted pathways around the grains, thus increasing the time for fragmentation to occur [11].…”
Section: Cone Formationsupporting
confidence: 92%
“…The damage mechanisms are common in all the compositions, but the volume of conical frustum may differ depending on the composition. Yamada et al [33] stated in their study that the volume of the cone is higher, and the energy consumed by surface formation is smaller in transgranular-fractured ceramics than in intergranular-fractured ones. Conversely, there will be usually a combination of the two failure modes, but this will depend on various effects like the packing structure, grain size, the strength of the grain boundary material, loading conditions (static or dynamic) [11,12].…”
Section: Cone Formationmentioning
confidence: 94%
“…The authors then suggested that for any set of surface flaws within the path of the cone crack, there exists a critical load for the initiation of a cone crack dependent on the fracture toughness of the ceramic, its elastic modulus and radius of the projectile. This fracture toughness is a combination of both the intergranular and trans‐granular fracture toughness of the ceramic material . The degree of quasi‐plasticity relative to the brittle mode can be altered by tailoring the ceramic microstructure …”
Section: Introductionmentioning
confidence: 99%
“…When B 4 C ceramics are used in these applications, they are susceptible to be impacted by foreign objects. Therefore, both the dynamic and static mechanical properties of B 4 C ceramics have been subject to studies widely . Previous studies have shown B 4 C ceramics to exhibit a high potential ballistic performance because of their high hardness and Hugoniot elastic limit (HEL) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown B 4 C ceramics to exhibit a high potential ballistic performance because of their high hardness and Hugoniot elastic limit (HEL) . However, B 4 C ceramics readily undergo catastrophic fracture because of their relatively low fracture toughness (of 2.8–3.3 MPam 1/2 ) in comparison with metals and other ceramics. Consequently, the brittleness of B 4 C ceramics is one of the serious challenges encountered in the application of these materials in high‐speed components and armors.…”
Section: Introductionmentioning
confidence: 99%